Development of Wireless Power Transfer for Low Voltage Application - Ismail, Muhammad Faizal; Harmizon, M. H.; Hui, L. D.; Wei, G. Z. (Multidisciplinary Applied Research and Innovation, 2020)
The development of wireless power transfer for low voltage application is proposed inthis paper. The main objective of this project is to transfer electrical energy wirelessly without connected by wire from source to load. Furthermore, this project aim to help on reduce cable wasted on the Earth, this is because wireless use lesser wire and doesn’t require to plug in and plug out frequently and help to tidy up mixed power cable of electronics. Then also achieve the effective range for wireless power transfer for more than direct touching (0cm). The concept of the wireless phone charger is using 2 copper coil which designed to transmit and receive voltage over air medium. It also use diode and capacitor on the receiver side to maintain a stable voltage over time to charge the phone. The projects will to reduce cable been throw away and easier the charging of mobile phone. Some practical studies on effect of coil diameter and range between transmitter, Tx and receiver, Rx has been done to figure out the optimum electrical energy transfer to the load, result was 2cm coil diameter had been selected as transmitter.